Persistence and decontamination of insecticide residues in polyhouse grown capsicum (Capsicum annuum) - CHANDEL, R S; PAL, V K; SHARMA, I D; PATYAL, S K (The Indian Journal of Agricultural Sciences, 2016)
The persistence and dietary intake of deltamethrin, endosulfan and malathion residues from coloured capsicum (Capsicum annuum L. var. Orobelle) grown under open ventilated polyhouse, was assessed after following common culinary processes. Each insecticide was applied at two concentrations, i.e. the recommended (single dose) and double the recommended doses. Insecticide residues were extracted using acetone and cleaned up over charcoal and Florisil columns. The determination and quantification of insecticide residues were done by using gas chromatograph equipped with ECD. The application of single dose, i.e. deltamethrin (0.0028%), endosulfan (0.05%) and malathion (0.05%) resulted in initial deposits of 0.667, 3.900 and 2.026 mg/kg; whereas, 0.937, 5.694 and 4.078 mg/kg at double dose, respectively, on capsicum fruits. The RL50 values were worked out as 1.90-2.41 days for deltamethrin, 1.75-1.88 days for endosulfan and 1.83 days for both the doses of malathion. Fruits washing under tap water for 1 minute provided relief of 30.05-38.81, 23.58-37.52 and 25.0-27.64% from deltamethrin, endosulfan and malathion residues, respectively, upto 3rd day, irrespective of doses. However, steaming after washing of the fruits provided maximum decontamination from insecticide residues. The endosulfan treated capsicum fruit consumption as salad revealed an appreciable risk to the consumers till 3rd day, whereas, washing+steaming reduced the dietary risk to the day of insecticide application.